2023
DOI: 10.1108/apjml-07-2022-0560
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting users' impulse purchases in online group buying: online consumer reviews, countdowns and self-control

Abstract: PurposeThis paper aims to investigate how online consumer reviews (OCRs), countdowns and self-control affect consumers' online impulse buying behavior in online group buying (OGB) and uncover the relationship between these factors.Design/methodology/approachBased on the stimulus-organism-response (SOR) framework, this research examines the effects of OCRs, countdowns and self-control on users' impulse purchases. First, the influence of emotions on impulse purchases in group purchasing is investigated. In addit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 55 publications
(102 reference statements)
0
9
0
Order By: Relevance
“…If consumers show a positive attitude towards online shopping, it will drive purchase intention. In addition, another study by Dewi, Mohaidin, and Murshid (2020) and Sun et al (2024) found that price, trust, product advertising and service quality influence and impact purchase intention. Previous studies have demonstrated that trust has a theoretical and empirical impact on customer intention.…”
Section: Consumer's Intention and Decision To Use Online Shopping Pla...mentioning
confidence: 99%
“…If consumers show a positive attitude towards online shopping, it will drive purchase intention. In addition, another study by Dewi, Mohaidin, and Murshid (2020) and Sun et al (2024) found that price, trust, product advertising and service quality influence and impact purchase intention. Previous studies have demonstrated that trust has a theoretical and empirical impact on customer intention.…”
Section: Consumer's Intention and Decision To Use Online Shopping Pla...mentioning
confidence: 99%
“…Whilst past studies (e.g. Besharat et al ., 2021; Sun et al ., 2023; Xiao, 2018; McCabe and Branco Illodo, 2019) suggest that enjoyment and variety-seeking are significant motivators for e-deal behaviour within a broader online coupon context, the lack of consensus across studies highlights the need to better understand how consumers evaluate e-deals and the impact of situational variables such as time and peer pressure on online purchasing behaviour (McCabe and Branco Illodo, 2019). Therefore, it is crucial for businesses in the hospitality industry to gain a deeper understanding of how consumers evaluate e-deals and the situational variables that influence their behaviour.…”
Section: Literature Theory and Hypothesesmentioning
confidence: 99%
“…Potential purchasers frequenting these websites often rely on indicators that amalgamate insights from prior consumers' interactions to shape their buying choices. Deal popularity is an example of such information cues (Sun et al ., 2023; Bae and Koo, 2018; Kao et al ., 2020). It shows the cumulative number of deals sold to consumers within a specific time duration (Ieva et al ., 2018; Luo et al ., 2014).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations